Surgical Treatment Options for Grafting Areas of Gingival Recession Association with Cervical Lesions: A Review. Issue 6 (17th September 2013) - Bignozzi, Isabella; Littarru, Cristiano; Crea, Alessandro; Vittorini Orgeas, Gianluca; Landi, Luca
Abstract Statement of the Problem Gingival recession (GR) is a highly prevalent dental problem that may be associated with dentin hypersensitivity and aesthetic complaint. Furthermore, GR is often complicated by dental cervical wear of substance, such as erosion, abrasion, or abfraction lesions, as well as initial or more extensive carious involvement of the cervical area, which worsen the symptoms and make the treatment of this periodontal condition more challenging. The Purpose of the Study To provide an overview of surgical treatment options presented in the literature for sites affected by GR with carious cervical lesions (CCLs) or non‐carious cervical lesions (NCCLs). Methods The Medline database was searched for items dealing with GR and its treatment options, especially on GR associated with CCLs or NCCLs. Results Several periodontal surgical techniques have shown good potential for treating GR over the years. Specifically, considering GR associated with CCL or NCCL, an assessment of both hard (dental) and soft (gingival) tissue characteristics of the involved site is recommended in selecting the surgical procedure. Conclusions For GR associated with CCL or NCCL, hard and soft tissue characteristics of the involved site have to be carefully evaluated in order to choose the most appropriate surgical procedure. Clinical Significance A structured decision‐making process, considering both hard and soft tissue characteristics of the involved site, is recommended in choosing the most appropriate surgical procedures to treat GR associated with CCL or NCCL defects. The restitutio ad integrum of the dento‐periodontal unit is an essential condition to restore the tooth to its original function and esthetics.